Access to All‐Carbon Spirocycles through a Carbene and Thiourea Cocatalytic Desymmetrization Cascade Reaction. (9th January 2019) - Zhuo, Shitian; Zhu, Tingshun; Zhou, Liejin; Mou, Chengli; Chai, Huifang; Lu, Yunpeng; Pan, Lutai; Jin, Zhichao; Chi, Yonggui Robin
Abstract: A new catalytic approach for rapid asymmetric access to spirocycles is disclosed. The reaction involves a carbene‐ and thiourea‐cocatalyzed desymmetrization process with the simultaneous installation of a spirocyclic core. The use of a thiourea cocatalyst is critical to turn on this reaction, as no product was formed in the absence of a thiourea. Our study constitutes the first success in the carbene‐catalyzed enantioselective synthesis of all‐carbon spirocycles. The reaction products can be readily transformed into sophisticated multicyclic molecules and chiral ligands. Abstract : Harmonische Katalysatoren : Duale Carben‐ und Thioharnstoffkatalyse ermöglicht einen schnellen asymmetrischen Zugang zu spirocyclischen Verbindungen durch einen Desymmetrisierungsprozess. Der Thioharnstoff‐Kokatalysator ist für diese carbenkatalysierte enantioselektive Synthese von Kohlenstoff‐Spirocyclen essenziell. Die Reaktionsprodukte können leicht in multicyclische Moleküle und chirale Liganden umgewandelt werden.